2014
DOI: 10.1177/0886260514539850
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Trait Anger, Childhood Physical Abuse, and Alcohol Consumption in Predicting Intimate Partner Aggression

Abstract: The current study examined three well-established risk factors for intimate partner aggression (IPA) within Finkel and Eckhardt’s I3 model, including two impellance factors—trait anger and childhood physical abuse history—and the disinhibiting factor of alcohol consumption. Participants were 236 male and female college students in a committed heterosexual dating relationship who completed a battery of self-report measures assessing childhood physical abuse, trait anger, alcohol consumption, and IPA perpetratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 39 publications
0
19
0
1
Order By: Relevance
“…Anger and alcohol-related problems were associated with IPV, by way of psychological aggression. Both anger and hazardous alcohol use have been implicated as risk factors for IPV in heterosexual couples (e.g., Finkel & Eckhardt, 2013; Maldonado, Watkins, & DiLillo, 2015). This is the first study to our knowledge to associate these variables with IPV among lesbian women.…”
Section: Discussionmentioning
confidence: 99%
“…Anger and alcohol-related problems were associated with IPV, by way of psychological aggression. Both anger and hazardous alcohol use have been implicated as risk factors for IPV in heterosexual couples (e.g., Finkel & Eckhardt, 2013; Maldonado, Watkins, & DiLillo, 2015). This is the first study to our knowledge to associate these variables with IPV among lesbian women.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies with different samples are also consistent with this hypothesis: individuals who experienced more trauma in their childhood may demonstrate anger and aggressive behavior. 3,4,13,14,60,61 In various studies, participants with history of physical, emotional and sexual abuse were found to have been increased levels of trait anger and externalized anger with lower anger control, compared to those without history of abuse. 21 Widom and Mazfield found a higher ratio of being arrested because of violent crimes in individuals with history of childhood abuse, compared to people without such a history.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Various findings in the literature suggest a relationship between abuse experiences and anger levels. 4,[14][15][16][17] Children who were exposed to domestic violence and abuse are thought to have a high risk of evolving into adults who act violently. 18 Moreover, children with abuse experiences were found to demonstrate reactions of anger and aggression frequently.…”
mentioning
confidence: 99%
“…This hypothesis is supported by the finding that animal abusers and individuals who engage in antisocial behavior share a number of unique characteristics, including aggression, poor impulse control, and exposure to interpersonal violence (Ascione, ANIMAL ABUSE PROCLIVITY 6 2005;Tapia, 1971). Moreover, drug use is known to result in behavioral disinhibition, which can precipitate aggressive and violent behavior (Maldonado, Watkins, & DiLillo, 2015).…”
Section: Animal Abuse As An Indicator Of Other Antisocial Behaviorsmentioning
confidence: 96%